Austrian Parliamentary Elections: Politics and Arithmetic - Vladimir Schweitzer (Научно-аналитический вестник Института Европы РАН, 2019)
The main result of the extraordinary parliamentary elections held on September 29, 2019 in Austria was the expected major victory of the Austrian people’s party (OVP) led by S. Kurtz. The electoral losses of the country’s other two leading parties, the Social Democrats (SPO) and the Austrian freedom Party (FPO), were also predictable. The positions of The Greens have strengthened, which corresponds to the general European political trend. However, the main question of the Austrian autumn 2019 – the formation of a new government – yet remains without a clear answer.